BCS: A Binary Cuckoo Search algorithm for feature selection - Rodrigues, D. [UNESP]; Pereira, L. A M [UNESP]; Almeida, T. N S [UNESP]; Papa, João Paulo [UNESP]; Souza, A. N.; Ramos, C. C O; Yang, Xin-She (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Feature selection has been actively pursued in the last years, since to find the most discriminative set of features can enhance the recognition rates and also to make feature extraction faster. In this paper, the propose a new feature selection called Binary Cuckoo Search, which is based on the behavior of cuckoo birds. The experiments were carried out in the context of theft detection in power distribution systems in two datasets obtained from a Brazilian electrical power company, and have demonstrated the robustness of the proposed technique against with several others nature-inspired optimization techniques. © 2013 IEEE.
Keywords: Binary cuckoo searches; Electrical power; Optimization techniques; Power distribution system; Theft detections; Electric load distribution; Feature extraction; Electric utilities